Effective Facilitated Peer Mentoring Model: From the Mentors’ Perspective - Al-Khathami, Abdullah Dukhail (European Journal of Applied Sciences, 2022)
Purpose:This study aimed to formulate a framework for a facilitated peer mentoring (FPM) program from the mentors’ perception; define the characteristics and roles of the facilitator and his/her mentors, successful FPM relationship, FPM program contents, and strategies for implementation. Methods:The population of the study comprised 19 junior family medicine trainers, who have experience as mentors, and were involved in a focus group study to formulate an FPM program structure. The author conducted this study in the postgraduate family medicine program in the Eastern Province-Ministry of Health, Saudi Arabia,2016. Spearman-test tested the coefficient correlation between the characteristics and roles of the facilitator and mentors; a p-value of 0.05 was a significant finding. Results: All participants concluded the answers to the discussion questions in four components: Effective facilitator characteristics and his/her roles; mentors’ characteristics and their roles. There is a positive correlation between these characteristics and roles (p-value= 0.018); successful mentoring relationship factors, contents of the formal FPM program; and a proposed applicable implementation plan. Conclusions: This research plays a role in exploring the FPM program contents and roles in a comprehensive way from the mentors’ point of view. It fills the gap in the literature about the FPM program structure in the academic institutes.